Effects of Obesity and Thrombophilia on the Risk of Abortion in Women Undergoing In Vitro Fertilization - Candeloro, Matteo; Di Nisio, Marcello; Ponzano, Adalisa; Tiboni, Gian Mario; Potere, Nicola; Tana, Marco; Rutjes, Anne W. S.; Porreca, Ettore (Frontiers in Endocrinology, 2020)
Introduction Obesity is associated with a higher risk of abortion in women undergoing in vitro fertilization (IVF). Whether thrombophilia amplifies this risk is currently unclear. The aim of this study was to evaluate the effects of thrombophilia on the risk of abortion in obese women treated with IVF. Methods Patient characteristics, presence of inherited or acquired thrombophilia, and comorbidities were prospectively collected before the procedure in consecutive women undergoing IVF. The primary outcome was the incidence of abortion among women who achieved a clinical pregnancy. Results A total of 633 non-obese and 49 obese Caucasian women undergoing IVF were included. 204 (32%) women achieved clinical pregnancy, of whom six had an ectopic pregnancy and 63 experienced an abortion. The incidence of abortion was higher in obese women compared to non-obese women after adjusting for age (64.3% vs. 29.3%, odds ratio [OR] 4.41; 95% CI 1.41 to 13.81). Women with one or more thrombophilia were at increased risk of abortion relative to those without thrombophilia (OR 2.70; 95% CI 1.34 to 5.45), and the risk seemed to be higher with hereditary (OR 5.12; 95% CI 1.77 to 14.8) than acquired thrombophilia (OR 1.92; 95% CI 0.52 to 5.12; p for interaction 0.194). Among obese women, the presence of one or more thrombophilia seemed associated with a substantially increased risk of abortion (unadjusted OR 14.00; 95% CI 0.94 to 207.6). Conclusions Obese women undergoing IVF have a high risk of abortion which seems further amplified by the concomitant presence of thrombophilia.